2008
DOI: 10.1038/nature07389
|View full text |Cite
|
Sign up to set email alerts
|

A fast, robust and tunable synthetic gene oscillator

Abstract: One defining goal of synthetic biology is the development of engineering-based approaches that enable the construction of gene-regulatory networks according to 'design specifications' generated from computational modelling. This approach provides a systematic framework for exploring how a given regulatory network generates a particular phenotypic behaviour. Several fundamental gene circuits have been developed using this approach, including toggle switches and oscillators, and these have been applied in new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,190
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,056 publications
(1,241 citation statements)
references
References 31 publications
30
1,190
0
6
Order By: Relevance
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
See 2 more Smart Citations
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
“…Not only can this shed light into which parameter configuration makes a topology oscillate, but also into how ''tunable'' a topology is, that is, how much the oscillatory response can be controlled by changing the parameters of the network. Tunability, as well as robustness, is a highly desirable feature in synthetic oscillators (Tsai et al 2008;Stricker et al 2008). We started our analysis by studying the distribution of the robustness among all three-component topologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tigges et al designed an oscillator to enable autonomous, self-sustained and tunable oscillatory gene expression in mammalian cells based on an auto-regulated transcription control circuit encoding a positive and a time-delayed negative feedback loop (Tigges et al, 2009). Using a modeled network architecture comprising linked positive and negative feedback loops, Stricker et al engineered a fast, robust and tunable genetic oscillator, whose robustness is achieved by introduction of a time delay in the negative feedback loop (Stricker et al, 2008). The synthetic oscillators provide insights into the dynamics of natural periodic processes and foster advances in the design of networks in future gene and cell therapies.…”
Section: Oscillatorsmentioning
confidence: 99%
“…For example, techniques of synthetic biology and systems biology [8][9][10][11][12][13] have made it possible to fabricate bacterial strains with engineered gene-regulation circuits that produce predefined spatial and temporal patterns. Similarly, artificial self-motile agents can be realized through catalytically driven Janus particles [14][15][16][17][18].…”
mentioning
confidence: 99%